Nilai-Nilai Dakwah dalam Ibadah Kurban - Sarkawi Sarkawi (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2022)
Worship, as it is known that the qurban worship is one of the highly recommended Worship, the event that the sacrificial worship begins with the story of the son of the Prophet Adam qabil and habil, as well as the story of the Prophet Ibrahim and Isma'il As, this worship certainly has wisdom and contains certain meanings and values. Likewise in the Da'wah study, however, when viewed from the statistics on the implementation of Qurban in Indonesia, it is only under 1% of the total population of Indonesia. This study wants to see how the value of Da'wah in Sacrifice Worship is, while the writing method used is to find literature and references related to qurban worship to be analyzed, from the results of this study it was found that there are at least three important points. 1) Giving the best in the way of Allah (2) an invitation to relieve each other's burdens (3) spending wealth in the way of Allah.